Enhancing accreditation outcomes for medical laboratories on the Strengthening Laboratory Management Toward Accreditation programme in Kenya via a rapid results initiative - Ernest P. Makokha; Raphael O. Ondondo; Daniel K. Kimani; Thomas Gachuki; Frank Basiye; Mercy Njeru; Muthoni Junghae; Marie Downer; Mamo Umuro; Margaret Mburu; Jane Mwangi (African Journal of Laboratory Medicine, 2022)
Background: Since 2010, Kenya has used SLIPTA to prepare and improve quality management systems in medical laboratories to achieve ISO 15189 accreditation. However, less than 10% of enrolled laboratories had done so in the initial seven years of SLMTA implementation.